Effect of carbon in Si oxide interlayers of the Al2O3/4H-SiC structure on interfacial reaction by oxygen radical treatment. (22nd February 2019) - Doi, Takuma; Takeuchi, Wakana; Shibayama, Shigehisa; Sakashita, Mitsuo; Taoka, Noriyuki; Nakatsuka, Osamu; Zaima, Shigeaki
Abstract: The interface state density of Al2 O3 /4H-SiC can be decreased by oxygen radical treatment at room temperature, so we have systematically investigated the mechanism of the interfacial reaction at Al2 O3 /4H-SiC during oxygen radical treatment. In this study we focus on the characteristics of the Si oxide interlayer, namely whether carbon atoms are included in the film or not, because the interfacial reactions induced by oxygen radical treatment for Al2 O3 /4H-SiC and Al2 O3 /Si are different. It is revealed that decarbonization of the SiC x O y layer occurs when the SiC x O y surface is directly exposed to oxygen radicals. Then, the difference in the interfacial reaction caused by oxygen radical treatment between Al2 O3 /4H-SiC and Al2 O3 /Si is investigated by intentionally forming SiC x O y and SiO2 interlayers at the Al2 O3 /4H-SiC interface. Finally, the possible reaction mechanism is discussed on the basis of experimental results. All the results are qualitatively (but clearly) understood by considering that decarbonization of SiC x O y occurs as the starting point.